ASSESSMENT OF ECG INTERPRETATION AMONG NURSES - NAZ , M; KARAMAT, N; SADDIQUE, H; TESNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Electrocardiography (ECG) is a vital diagnostic tool for the early identification and management of cardiac conditions. Nurses, as integral members of the healthcare team, require strong ECG interpretation skills to ensure timely and accurate patient care. However, gaps in knowledge, training, and practice remain significant challenges, particularly in resource-constrained settings. Objective: To assess the knowledge, confidence, and practices of nurses regarding ECG interpretation and identify gaps and barriers to effective training and utilization. Methods: A cross-sectional study was conducted at Mayo Hospital, Lahore, over three months. A purposive sampling technique was used to recruit 134 registered nurses from the Cardiology, Medicine, and Gynecology departments. Data were collected using a structured questionnaire and analyzed using SPSS version 22. Descriptive and inferential statistics, including central tendency measures and p-values, were employed to summarize and assess trends within the data. Results: Moderate confidence in ECG interpretation was reported by 26.1% of participants, while 17.2% strongly disagreed with their confidence levels. Perceptions of training adequacy were mixed, with 23.9% strongly agreeing that their education was sufficient, but 19.4% strongly disagreed. Regular utilization of ECG interpretation skills in clinical practice was reported by only 20.1%. A notable demand for additional training was observed, with 39.6% of respondents advocating for refresher courses. Workplace and peer support were identified as critical factors influencing skill utilization and development. Conclusion: Nurses’ knowledge and confidence in ECG interpretation remain suboptimal, reflecting gaps in training and limited clinical application. Targeted educational interventions, workplace support, and the incorporation of innovative tools are essential to enhance ECG interpretation competencies. These measures will empower nurses to deliver improved cardiac care and contribute to better patient outcomes.